Metode Pendidikan Islam dalam Keluarga (Tinjauan Pedagogis dan Psikologis terhadap Keluarga Nabi) - Af'idah, Gina Hana; Kamal, Mustopa; Darisman, Dede (Graduate Program, Darussalam Institut for Islamic Studies, 2018)
This article is the result of a study of a number of historical literature of the Prophet Muhammad. Some of the results of this research article are that the education within the family run by the Prophet along with his wife is based on the principle of justice, educate with affection, proportionally punish, educate with exemplary, carry out education long before the child is born, and create a religious atmosphere in educational environment